A dominant electron trap in molecular beam epitaxial InAlN lattice-matched to GaN. (12th March 2018) - Pandey, Ayush; Bhattacharya, Aniruddha; Cheng, Shaobo; Botton, Gianluigi A; Mi, Zetian; Bhattacharya, Pallab
Abstract: Deep levels in lattice-matched undoped and Si-doped InAlN/GaN grown by plasma-assisted molecular beam epitaxy have been identified and characterized by capacitance and photocapacitance measurements. From x-ray diffraction, reflectance measurements, electron energy loss spectroscopy and high-resolution transmission electron microscopy it is evident that the material has two distinct phases with different compositions. These correspond to In compositions of 18.1% and 25.8%, with corresponding bandgaps of 4.6 eV and 4.1 eV, respectively. The lower bandgap material is present as columnar microstructures in the form of quantum wires. A dominant electron trap with an activation energy of 0.293 ± 0.01 eV, a small capture cross-section of (1.54 ± 0.25) × 10 −18 cm 2, and density increasing linearly with Si doping density is identified in all the samples. The characteristics of the electron trap and variation of diode capacitance are discussed in the context of carrier dynamics involving the dominant trap level and the quantum wires.